" The effectiveness of public relations practitioners in managing social media platforms of Iraqi satellite channels" A field study. - Karrar Haider Hatef, Asst. Lect. (lark, 2025)
The research is summarized in the researcher’s quest to know the effectiveness of public relations practitioners in managing social media platforms of Iraqi satellite channels, as well as identifying their skills in managing these communication platforms, while the problem of the research lies in knowing the extent of the effectiveness of public relations practitioners in managing social media platforms in satellite channels. As for this research, it is a descriptive research, as the researcher relied on the survey method based on surveying the media with a deliberate sample of (20) individuals from public relations practitioners in a number of Iraqi satellite channels that were represented in the research sample. The aim of the research focuses on determining the extent of the ability of public relations practitioners to provide the public with accurate information by publishing it on social media platforms, in addition to answering the public’s questions and providing them with the information they need. The researcher recommended that there should be interest by satellite channels in public relations practitioners to develop their scientific and professional skills to achieve the highest levels of effectiveness in managing social media platforms.